Australian Public Library Staff Living through a Pandemic: Personal Experience of Serving the Community. Issue 3 (3rd July 2021) - Wilson, Maree
ABSTRACT: The 2020 COVID-19 pandemic forced public library staff to rapidly rethink the services they offered as lockdown restrictions meant that libraries as social venues briefly came to an end. Online content was developed overnight to fill the void. This study examines the impact that the contactless operational model has had on library services across Australia, as seen through the eyes of eight public library staff. The qualitative study contributes in-depth data to scant literature about public libraries and the pandemic in an Australian context. The study highlights the value of libraries to the community. The need for in-person contact is discussed in terms of future service design in library and information practice.